AN EXAMINATION ON INFORMATION MINING INNOVATION AND EXECUTING OF AN INFORMATION DIGGING APPLICATION FOR DEALS PRESCIENT INVESTIGATION - Johar; MSM; Azam, S.M. Ferdous; Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
Amway (M) has been taken into account in context of Data Mining technology and implementation of predictive analysis of sales. The references at this stage are mainly books, journals and articles on the Internet about Data Mining, as well as interviews and observations which are carried out to obtain the necessary information about Amway (M). The second part of this project is on the analysis of the data obtained. The analysis was done based on the database constructed. A model is built after this, as a guide to the real implementation in the later stage. The application developed was mainly to have the comparative studies showed here in visual forms. Various types of graphics were adopted in this program as to visualize the comparisons of the figures. Testing was well carried out after the development of the application. Testing was done as to ensure that this program worked well in the specified platform. Reports were produced based on the testing procedures.